2009
DOI: 10.1128/aem.02659-08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Starvation on a Host Bivalve (Codakia orbicularis, Lucinidae) and Its Symbiont Population

Abstract: The bivalve Codakia orbicularis, hosting sulfur-oxidizing gill endosymbionts, was starved (in artificial seawater filtered through a 0.22-m-pore-size membrane) for a long-term experiment (4 months). The effects of starvation were observed using transmission electron microscopy, fluorescence in situ hybridization and catalyzed reporter deposition (CARD-FISH), and flow cytometry to monitor the anatomical and physiological modifications in the gill organization of the host and in the symbiotic population housed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 52 publications
3
42
0
Order By: Relevance
“…In the laboratory, it is possible to maintain adult bivalves under starvation conditions for up to 6 months and minimize the number of symbionts inside the gills. During our experiments, the appearance of the lucinid gills changed from thick and lightly beige in freshly collected bivalves (containing large symbiont populations with a large quantity of elemental sulfur) to thin and dark brown in starved bivalve individuals (containing fewer symbionts without elemental sulfur) (personal observations) (Caro et al, ; Lechaire et al, ; Pflugfelder et al, ). We suggest that the host can use this large amount of bacteria as a nutrient source through lysosomal degradation (Johnson and Fernandez, ).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the laboratory, it is possible to maintain adult bivalves under starvation conditions for up to 6 months and minimize the number of symbionts inside the gills. During our experiments, the appearance of the lucinid gills changed from thick and lightly beige in freshly collected bivalves (containing large symbiont populations with a large quantity of elemental sulfur) to thin and dark brown in starved bivalve individuals (containing fewer symbionts without elemental sulfur) (personal observations) (Caro et al, ; Lechaire et al, ; Pflugfelder et al, ). We suggest that the host can use this large amount of bacteria as a nutrient source through lysosomal degradation (Johnson and Fernandez, ).…”
Section: Discussionmentioning
confidence: 67%
“…In deep sea bivalves, it was suggested that lysosomal symbiont digestion is a way of controlling symbiont populations (Fiala‐Medioni et al, ). During starvation, lysosomes in the gills of both Codakia species become larger and more abundant (Caro et al, ). Moreover, Elisabeth et al () described a massive decrease in the area occupied by bacteriocytes in C. orbiculata during starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of the latter include Lucinoma borealis , Myrtea spinifera, Lucinoma aequizonata, and Lucina floridana (Anderson, 1995), Thyasira sp. (Southward et al, 2001), Lucinoma aequizonata and Parvilucina tenuisculpta , and Codakia orbicularis (Caro et al, 2009). The chemical components, such as glycerolipids, have yet to be elucidated for these clams, except in the case of R. philippinarum from European coastal waters (Kraffe et al, 2004;Delaporte et al, 2005;FernĂĄndez-Reiriz et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Recent morphological and molecular analyses (Elisabeth et al ., ; Gros et al ., ) support the conclusion that it is possible to induce complete or nearly complete loss of symbionts in adult lucinids by depriving their symbionts of their energy source (mainly in sulphide‐free environment). Decreases in endosymbiont abundance within gill cells have been shown according to structural investigations of the gill tissue in other chemosynthetic bivalves such as thyasirids (Dufour & Felbeck, ), vesicomyids (Goffredi et al ., ), bathymodiolin (KĂĄdĂĄr et al ., ) and two lucinids (Caro et al ., ; Gros et al ., ). However, no data are available concerning the modifications undergone by the endosymbionts themselves (at the metabolic or genomic level) during increase or decrease of their populations within the gill tissue either in the frame of starvation laboratory experiments or in their natural habitats.…”
Section: Introductionmentioning
confidence: 98%